Laparoscopic Transhiatal Thoracic Duct Ligation for Chylothorax after Esophagectomy - Yamagata, Yukinori; Saito, Kazuyuki; Hirano, Kosuke; Oya, Masatoshi (The Thoracic and Cardiovascular Surgeon, 2019)
In esophagectomy for thoracic esophageal cancer, chylothorax may develop at a certain frequency. For chylothorax, conservative treatment is selected first, but if it is not improved, thoracic duct (TD) ligation is considered. In general, transthoracic approach is chosen to reach the TD. However, it is sometimes difficult to identify the TD due to adhesion in the thoracic cavity. Hence, we selected a laparoscopic transhiatal approach to the TD. We introduce the procedure of our laparoscopic transhiatal TD ligation technique.
Keywords: thoracic duct; mediastinum; esophageal; surgery